Enhancing Educational Practices: Digital Map Exploration For Senior High School Teachers - Adhityo Kuncoro; Dyah Rhetno Wardhani; Vickry Ramdhan; Rahman Abdillah; Fajar Erlangga (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This article discusses the implementation of a Google Earth training program for teachers at SMA Putra Bangsa Depok as part of an effort to develop technological skills in education. The training aimed to assist teachers in integrating technology into their teaching practices in line with Kurikulum Merdeka (Merdeka Curriculum), which emphasizes student-centered learning and the use of digital tools to enhance student engagement and understanding. The program included an introduction to Google Earth features, hands-on training, and an evaluation of the training outcomes. Although the training received positive feedback from the teachers, challenges such as limited time and inadequate equipment were identified. Therefore, it is recommended to conduct follow-up training sessions, provide ongoing support, and form a dedicated team focused on developing technology in education to ensure the optimal and sustainable use of this tool.